The Effectiveness of the Green Activity Program in Improving Pro-Environmental Consumer Behavior in Elementary School Students - Rahmawati, Deasy; Supriatna, Nana; Sapriya, Sapriya (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to examine the effectiveness of green activity programs in shaping the pro-environmental consumer behavior of elementary school students. The program was implemented as part of the Pancasila Student Profile Strengthening Project within the independent curriculum framework. The study involved 71 fifth-grade students from three public elementary schools in Bandung: SDN 240 Cijerah Indah, SDN 099 Babakan Tarogong, and SDN 191 Babakan Surabaya. The program was conducted over four weeks and included waste sorting, composting, recycling, energy-saving campaigns, and vegetable planting. A one-group pretest-post-test pre-experimental design was used, and data were collected through a green consumer behavior questionnaire assessing five behavioral stages: product search, purchase, usage, evaluation, and disposal. Quantitative analysis using paired sample t-tests showed a statistically significant improvement in students’ behavior (p < 0.001), with an average increase in scores ranging from 15.45 to 22.74 points across schools. The N-Gain analysis revealed moderate learning gains, with values between 0.558 and 0.563. These findings confirm the effectiveness of green activity programs in fostering pro-environmental consumer behavior. The study recommends implementing similar programs in other schools and conducting further research to assess long-term behavioral impacts and contributing factors. This research has implications for developing environmental education strategies that cultivate sustainable habits from an early age.